A Flickering Stimuli Method for Investigating Temporal Features of Binocular Vision - Noreika, D.; Vaitkevičius, H.; Švegžda, A.; Vanagas, V.; Stanikūnas, R.; Bliznikas, Z. (Elektronika ir Elektrotechnika, 2010)
A flickering stimuli method for investigating temporal features of binocular vision is introduced and experimental results of the use of the method for investigating binocular rivalry are presented. Binocular rivalry is a phenomenon of visual perception in which perception alternates between two different images, presented to each eye. The results attest, that the new method and apparatus are suitable for investigating the temporal characteristics of binocular rivalry in an accurate and reliable way. The flash duration of the stimuli influences the dominant time of binocular rivalry. The first peak of the dominance duration curve (3,5 s – 4,5 s) mostly occurs in the 7 ms – 10 ms interval.